List of IMF Member Countries with Delays in Completion of Article IV Consultations Over 18 Months or Mandatory Financial Stability Assessment Over 18 Months. (Policy Papers; Policy Paper ;, 2015)
This Staff Report Lists IMF Member Countries with Delays in Completion of Article IV Consultations over 18 Months or Mandatory Financial Stability Assessment over 18 Months, prepared by IMF staff and completed on January 28, 2015.